Hemithioindigo‐Based Visible Light‐Activated Molecular Machines Kill Bacteria by Oxidative Damage - Ana L. Santos; Alexis vanVenrooy; Anna K. Reed; Aaron M. Wyderka; Víctor García‐López; Lawrence B. Alemany; Antonio Oliver; George P. Tegos; James M. Tour (Advanced Science, 2022)
Abstract Antibiotic resistance is a growing health threat. There is an urgent and critical need to develop new antimicrobial modalities and therapies. Here, a set of hemithioindigo (HTI)‐based molecular machines capable of specifically killing Gram‐positive bacteria within minutes of activation with visible light (455 nm at 65 mW cm−2) that are safe for mammalian cells is described. Importantly, repeated exposure of bacteria to HTI does not result in detectable development of resistance. Visible light‐activated HTI kill both exponentially growing bacterial cells and antibiotic‐tolerant persister cells of various Gram‐positive strains, including methicillin‐resistant S. aureus (MRSA). Visible light‐activated HTI also eliminate biofilms of S. aureus and B. subtilis in as little as 1 h after light activation. Quantification of reactive oxygen species (ROS) formation and protein carbonyls, as well as assays with various ROS scavengers, identifies oxidative damage as the underlying mechanism for the antibacterial activity of HTI. In addition to their direct antibacterial properties, HTI synergize with conventional antibiotics in vitro and in vivo, reducing the bacterial load and mortality associated with MRSA infection in an invertebrate burn wound model. To the best of the authors’ knowledge, this is the first report on the antimicrobial activity of HTI‐based molecular machines.